LIPID METABOLISM AND THYROID HORMONE : A REVIEW - USHA S ADIGA; SACHIDANANDA ADIGA (International Journal of Pharma and Bio Sciences, 2013)
Thyroid hormone , secreted by thyroid gland have a profound effects on the lipid metabolism. It exerts its action mainly by its genomic action. It diffuses from the extracellular fluid across the plasma membrane and go directly into the nucleus. The cognate receptor binds to the thyroid hormone response element [TRE].It regulates the gene expression of key enzymes involved in lipid metabolism by modulating their transcription.Thyroid hormone induces acetyl CoA carboxylase,fatty acid synthase,malic enzyme and thereby favours fatty acid synthesis.Paradoxically it also favours oxidation of fatty acids by enhancing the expression of carnitine palmitoyl transferase.Thyroid hormone is closely associated with lipoprotein metabolism,known to decrease triglycerides by enhanced activity of lipoprotein lipase and hepatic lipase activities.It is universally accepted that this hormone lowers cholesterol content of low density lipoprotein by affecting the expression of LDL receptors and clearance of LDL.It also has important role in stabilizing the mRNA coding for the rate limiting enzyme of cholesterol biosynthesis, HMG CoA reductase. Cholesterol clearance is affected as this hormone influences the enzymes of bile acid synthesis.This review discusses the effect of thyroid hormone in lipid metabolism in detail and lipid variations that occur in hypo and hyperthyroid conditions. The effects of thyroid hormone on the lipid metabolism makes it a potential molecule to develop a class of drugs which can modify the lipid levels.Clinical trials are going on to test the use of thyroid hormone analogues in the treatment of hyperlipidemias.